Promosi pariwisata budaya dan ekowisata di wilayah perbatasan: Analisis SWOT dan strategi pengembangan di Kabupaten Malaka - Odilia Muti; Maria Imakulata Pongge; Marius Masri (Journal of Economics Research and Policy Studies, 2026)
This study examined the promotion of cultural tourism and ecotourism in Malaka Regency, a border area between Indonesia and Timor-Leste. The main problems identified were suboptimal destination promotion, limited facilities, low use of digital media, and weak integration between cultural and natural tourism potential. This study employed a qualitative descriptive approach using observation, interviews, focus group discussions, and documentation. The data were analyzed using a SWOT matrix to identify the strengths, weaknesses, opportunities, and challenges of tourism promotion. The findings showed that Malaka Regency had strong potential in Likurai and Bidu traditional dances, woven textiles, traditional houses, Motadikin Beach, Abudenok Beach, and community involvement. The main weaknesses were limited accessibility, inadequate facilities, cleanliness issues, budget constraints, and limited human resource capacity. Development opportunities emerged through digital promotion, cultural festivals, and integrated cultural-ecotourism packages. The main challenges involved competition with other destinations, climate change, and uneven public awareness. This study concluded that tourism promotion should integrate cultural and natural attractions through community, government, and digital media support.